Improvement of control of construction and installation works - Osmyatchenko, Volodymyr; Pinchuk, Kateryna (Herald of Economics, 2020)
Introduction. Effective activity in the construction of business entities enhances competitiveness and enhances their ability to reproduce production and economic activity on an innovative basis. At the same time, mistakes and abuse during the recording of construction operations cause not only a distorted idea of the scale and results of construction activity, but also cause losses and penalties for violations detected by the control bodies. Effectively adjusted control of construction works is the basis for making economically sound investment-innovation and management decisions. The theoretical and methodological aspects of the control of construction work in the construction or improvement of fixed assets need improvement. The purpose of the article is to critically analyze the existing problems of control of economic operations in the construction process and to improve the assets of fixed assets and to improve the order of control of construction works. Method (methodology). In the course of the research the following methods were used: dialectical, generalization, comparison, system analysis, observation of economic activity, graphic, etc. Results. The essence of control as one of the control functions is considered. It is justified that control is a system of observation and verification of the process of functioning and the actual state of the control object in order to make effective management decisions. It is proved that the method of control of construction works depends on the organizational and economic forms of the process of construction production, a large number of participants having different functional goals and tasks, and also depending on the process of construction production on the natural conditions. The peculiarities of control of BIS operations carried out in a contractual, economic and mixed way are considered. It is substantiated that to prevent violations in construction requires a systematic approach to the implementation of interrelated accounting and control procedures for investing in contracting and business methods of organization of construction, especially in the conditions of functioning of information networks for accounting purposes. It is determined that by eliminating contradictions and strengthening the consistency between accounting and control work will increase the reasonableness of prices for construction products, will solve a number of problems related to the correctness of displaying the initial cost of objects after their completion, refurbishment and reconstruction, increase reliability and the quality of the fixed assets that have been invested, and the financial discipline in the investment and construction sector. The problems of construction and installation work control in building and the suggested recommendations for their solution provide the basis and prospects for further research in the field of improvement of accounting, analysis and control of the activity of construction enterprises.